A feasibility study of Augmented Reality Intervention for Safety Education for farm parents and children - Namkoong, Kang; Leach, John; Chen, Junhan; Zhang, Jiawen; Weichelt, Bryan (Frontiers in Public Health, 2023)
Agriculture is one of the most dangerous U.S. occupations with high rates of injuries and fatalities, and especially more dangerous for children, having more young worker deaths than any other industry. Thus, safety education is essential in promoting safe and healthy working habits in agriculture. Augmented reality (AR) technology has great potential to enhance the effectiveness of safety education due to its high levels of system-user interactivity and media enjoyment. This study aims to: (1) develop Augmented Reality Intervention for Safety Education (ARISE), an AR 3D simulator that presents farm accident situations with immersive media technology, (2) examine the feasibility of ARISE, and (3) evaluate the potential of ARISE as an effective agricultural safety education program for farm parents and children. To test the feasibility of ARISE, we conducted semi-structured in-depth interviews with ten parent-child dyads at an extension office located in Maryland. Participants were farmers who owned and operated a family farm(s) with their child or children ages 5–13. The interviews included asking participants questions about their perceptions of farm risks, sources of risk education, and protection methods. In the next step, participants used ARISE with researcher guidance. After using the application, participants were asked questions about their experience using ARISE and suggestions for improvement. The interviews were then transcribed and analyzed following the conventional content analysis method. Three main themes emerged—demand (e.g., perceived risk and need for education; lack of farm safety education from school), acceptability (e.g., attitude toward AR technology; perceived realism; perceived ease of use; perceived usefulness), and implementation. These findings help us understand how an immersive experience can play an impactful role in enhancing agricultural safety. The feasibility of ARISE sheds light on the potential of AR technology for an innovative safety education program.